The Influence of Social Media and Marketplace on the interest in Buying Bima Woven Fabric Products - Jannah, Miftahul (Universitas Trilogi, 2022)
The globe has become borderless as a result of the rapid development of information and communication technologies. People even use the internet as a means of buying and selling products and services online, which was subsequently referred to as the online market. The internet has evolved to adapt to the demands of the community and people even use the internet as a method of doing so. The Bima weaving company group use web marketing to supplement their sales efforts. The objective of this research is to investigate the role that social media and online marketplaces have in shaping consumer interest in purchasing bima weaving items. The data were acquired via the use of an online questionnaire, and there were a total of one hundred people that responded to the survey. sampling carried out utilizing the method of purposive sampling Excel 2013 and SPSS 22 for Windows are the programs that are used to handle the data. Quantitative research methodologies and multiple linear regression analysis are used in this work. This demonstrates that there is a beneficial influence that social media has on purchase interest. It is possible to draw the conclusion that there is a tight association between the independent and dependent variables as a result of the fact that the correlation value between the social media and marketplace variables from the purchasing interest variable is 75%. According to the findings of the t-test, the desire to purchase bima weaving items is significantly impacted by the use of social media. The marketplace is a crucial factor in determining the degree of purchaser interest in bima weaving items. According to the findings of the F test, the combination of the market and social media has a substantial impact on the amount of interest buyers have in purchasing Bima woven items.